DLE Progressing to Squamous Cell Carcinoma: A Case Report - S. Karki; A.K. Jha (Nepal Journal of Dermatology, Venereology & Leprology)
A 90 years female diagnosed as a case of Discoid lupus erythematosus (DLE) developed Squamous cell carcinoma from the lesions over a period of 5 years due to treatment gap and late follow up. Diagnosis was based on clinical aspects (erythematous, nodular and scanty bleeding), dermoscopic features and histopathological examination, the absence of systemic involvement and routine laboratory parameters, which registered all within normal range.